2017
DOI: 10.5120/ijais2017451709
|View full text |Cite
|
Sign up to set email alerts
|

Developing Virtual Class Room Models with Bio Inspired Algorithms for E-Learning: A Survey for Higher Technical Education for Saudi Arabia Vision 2030

Abstract: In recent times there has been a growing trend for more information and knowledge to enhance learning based on cognitive load theory with increased use of Educational Technology based on Web ICT with online education resources. There are also various instructional and expert models being developed for the adaptive e-learning mechanisms as required for effective learning based on Genetic, Neural Networks, Swarm Intelligence and other Bio inspired algorithms or Evolutionary algorithms. Computational Intelligence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The habit like taking tea or coffee makes sense at a study [47] conducted in 2017, explored the link between personality type and blood group. As per the study [48] it is concluded that there is a strong correlation between Introvert and Extravert type people with their learning styles. The Chatbot interacts with the learners to classify them into Introverts and Extraverts.…”
Section: Proposed Methodsmentioning
confidence: 72%
“…The habit like taking tea or coffee makes sense at a study [47] conducted in 2017, explored the link between personality type and blood group. As per the study [48] it is concluded that there is a strong correlation between Introvert and Extravert type people with their learning styles. The Chatbot interacts with the learners to classify them into Introverts and Extraverts.…”
Section: Proposed Methodsmentioning
confidence: 72%
“…The results concluded that the headway and integration of a DSS with the higher education might settle on a compact outlay and anticipated time that would focus on the critical issues of drafting and grasping the most appropriate decisions (Fakeeh 2015).…”
Section: ) Published In the Academic Journal Of Interdisciplinary Stu...mentioning
confidence: 99%
“…Management-centred DSSs are commonly dealing with general aspects of higher education administration and support existing institutional processes (Kasap et al, 2020;Nieto et al, 2019a;Ploywattanawong, 2016). However, existing DSSs do not adequately address institutional strategic planning and development (Fakeeh, 2015;Nieto et al, 2019b), meaning that there is a lack of systems designed to aid TLCs or similar strategic units in making informed decisions about complex processes, such as innovations in teaching and learning or strategic planning and development (Albon et al, 2016;Atkins et al, 2017).…”
Section: Introductionmentioning
confidence: 99%